Impact of prophylactic platelet transfusions on bleeding events in patients with hematologic malignancies: a subgroup analysis of a randomized trial. - Stanworth, S; Estcourt, L; Llewelyn, C; Murphy, M; Wood, E (2014)
BACKGROUND: A recent randomized trial compared a policy of no prophylaxis with a policy of prophylactic platelet (PLT) transfusions at counts of fewer than 10 × 10(9) /L in patients with hematologic malignancies. The results suggested the effectiveness of prophylactic PLT transfusions may vary according to patient diagnosis and treatment plan. STUDY DESIGN AND METHODS: This article presents full subgroup analyses and compares treatment effects between autologous hematopoietic stem cell transplantation (autoHSCT; n = 421) and chemotherapy/allogeneic HSCT (chemo/alloHSCT; n = 179) patients. RESULTS: Prespecified subgroup analysis found that the reduction in proportion of patients experiencing WHO Grade 2 to 4 bleeds (main trial outcome) seen in the prophylaxis arm was of greater magnitude in chemo/alloHSCT than autoHSCT patients (interaction p = 0.04). Analysis of secondary outcomes showed a shorter time to first bleeding episode with no prophylaxis in the chemo/alloHSCT group (hazard ratio, 1.84; 95% confidence interval CI, 1.21-2.79; p = 0.004) compared to the autoHSCT group (hazard ratio, 1.12; 95% CI, 0.85-1.48; p = 0.4; interaction p = 0.08). The increased number of days with Grade 2 to 4 bleeds with a no-prophylaxis policy was similar in chemo/alloHSCT (rate ratio, 1.89; 95% CI, 1.10-3.26) and in autoHSCT patients (rate ratio, 1.43; 95% CI, 1.04-1.97). Both subgroups showed significant reductions in PLT transfusions with a no-prophylaxis strategy. CONCLUSION: There is evidence that the effectiveness of prophylactic PLT transfusions may differ between subgroups, with chemo/alloHSCT patients receiving prophylactic PLT transfusions appearing to show a greater reduction in bleeding outcomes compared to patients following a no-prophylaxis policy.